Pengaruh Penggunaan Silica Fume Sebagai Bahan Tambah Pada Beton Alir - Achmad ihza Mahendra; Nurul Rochmah; Herry Widhiarto (Pusat Riset dan Inovasi Nasional, 2023)
Concrete is a material that is commonly used when doing construction work today. Because concrete has several advantages when compared to other materials, such as being easy to form, resistant to weather changes, has high compressive strength, and is durable. In this study the use of Silica Fume as an additive to flow concrete has the function of improving the quality of flowing concrete. Silica Fume has an important role in affecting the chemical and mechanical properties of concrete. Judging from its chemical properties, Silica Fume geometrically fills the voids between cement materials, and causes the pore diameter to decrease and the total pore volume to decrease. Meanwhile, from its mechanical properties, Silica Fume has a pozzolanic reaction (a material containing silica/silica dioxide and alumina compounds) which reacts to the limestone released by the cement. The aim of the research is to increase the maximum compressive strength of flowing concrete by using Silica Fume added with varying percentages of 0%, 5%, 6%, 7.5%, 9%, 10.5% and 12% and using a superplasticizer of 1.5 %. From the results of the research conducted, it was found that flowing concrete with added silica fume on concrete compressive strength was able to reach 7.5% at 7 days of age of 25.91 MPa and at 28 days of concrete age was obtained at 26.19 MPa.